Defining compassion in the digital health age: protocol for a scoping review. Issue 2 (15th February 2019) - Wiljer, David; Charow, Rebecca; Costin, Helen; Sequeira, Lydia; Anderson, Melanie; Strudwick, Gillian; Tripp, Tim; Crawford, Allison
Abstract : Introduction: The notion of compassion and compassionate care is playing an increasingly important role in health professional education and in the delivery of high-quality healthcare. Digital contexts, however, are not considered in the conceptualisation of compassionate care, nor is there guidance on how compassionate care is to be exercised while using digital health technologies. The widespread diffusion of digital health technologies provides new contexts for compassionate care, with both opportunities for new forms and instantiations of compassion as well as new challenges. How compassion is both understood and enacted within this evolving, digital realm has not been synthesised. Methods and analysis: This scoping review protocol follows Arksey and O'Malley's methodology to examine dimensions of compassionate professional practice when digital technologies are integrated into clinical care. Relevant peer-reviewed literature will be identified using a search strategy developed by medical librarians, which applies to six databases of medical, computer and information systems disciplines. Eligibility of articles will be determined using the two-stage screening process consisting of (1) title and abstract scan, and (2) full-text review. Screening, abstracting and charting will be conducted by two independent reviewers, with a third reviewer available for resolution when consensus is not achieved. In order to look at the range of current research in this area, extracted data will be thematically analysed and validated by content experts. Descriptive statistics will be calculated where necessary. Ethics and dissemination: Research ethics approval and consent to participate is not required for this scoping review. The results of the review will inform resource development and strategy for Associated Medical Services (AMS) Healthcare, a Canadian charitable organisation at the forefront of advancing research and leadership development in health and humanities, as part of the AMS Phoenix Project: A Call to Caring, particularly for digital professionalism frameworks so that they are inclusive of a compassion competency.